Mechanical Properties of Steels for Cold-Formed Steel Structures at Elevated Temperatures - Zhen Nie; Yuanqi Li; Yehua Wang (Advances in Civil Engineering)
It is highly important to clarify the high-temperature mechanical properties in the design of cold-formed steel (CFS) structures under fire conditions due to the unique deterioration feature in material properties under fire environment and associated reduction to the mechanical performance of members. This paper presents the mechanical properties of widely used steels for cold-formed steel structures at elevated temperatures. The coupons were extracted from original coils of proposed full annealed steels (S350 and S420, with nominal yielding strengths 280 MPa and 350 MPa) and proposed stress relieving annealed steels (G500, with nominal yielding strength 500 MPa) for CFS structures with thickness of 1.0 mm and 1.2 mm, and a total of nearly 50 tensile tests were carried out by steady-state test method for temperatures ranging from 20 to 700°C. Based on the tests, material properties including the yield strengths, ultimate strengths, the elasticity modulus, and the stress-strain curve were obtained. Meanwhile, the ductility of steels for CFS structures was discussed. Then, the temperature-dependent retention factors of yield strengths and elasticity modulus were compared to those provided by design codes and former researchers. Finally, a set of prediction equations of the mechanical properties for steels for CFS structures at elevated temperatures was proposed depending on existing tests data.